THEORY OF BIOHAPPINESS AND GENETIC VIRTUE OF MARK WALKER - Julia V. Khvastunova (Russian Studies in Culture and Society)
Mark Walker, one of the ideologists of modern transhumanism, developed a number of neuroethics provisions for the implementation of the “human enhancement” project. The basic elements of “making happy” are neurovirtues mediated by the introduction of genetic engineering (the creation of “happy-people-pills” (HPP)). The methodological basis or norm for genetic engineering is proposed to use the type of hyperthymic people. In the concept, there is some repetition of the ideas of O. Huxley’s novel “Brave New World”, where residents use soma, have the corrected nature of “genetic virtues”, and are in a state of controlled “ignorance”, happiness, and peace. M. Walker formulates his solution to O. Huxley’s dilemma (the choice between happiness and perfection) through the legalization and improvement of HPP. However, the interpretation of happiness itself is not satisfactory for transhumanists, since it comes down solely to neuroreduction and positive arguments for the use of radical technologies, including the programs which launch irreversible processes.